Penampilan produksi ayam pedaging yang dipelihara pada lantai atas dan lantai bawah - R. Dharmawan; H. S. Prayogi; V. M. A. Nurgiartiningsih (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2016)
This research aimed to study the performance of broiler raised in 3 stair floors. This research had been done from 09 September to 12 Oktober 2016 at Purwosari, Pasuruan. The data of performance was obtained from a poultry house which divided into 3 floors. The brooding period was given for 2 weeks in 2nd floor, on 15th days the chicken were separated into 1st and 3rd floor with the same house density. The obtained data was analyzed using T-test (independent samples T-test) to see the difference in between. The result of this research showed that there were highly significant differences on body weight gain, slaughter weight, and feed conversion ratio of broiler between 1st and 3rd floor. However, the differences floor did not contribute to differences on feed consumption (2.357 g/bird on 1st floor and 2.351 g/bird on 3rd floor). The body weight gain of broiler at 1st floor (1.293±96.52 g/bird) was lower than 3rd floor (1.331±82.77 g/bird). The final weight of broiler at 1st floor (1.780±90.6 g/bird) was lower than 3rd floor (1.818±81.8 g/bird). Feed conversion ratio of broiler at 1st floor (1.83±0.14) was higher than 3rd floor (1.77±0.11). The conclusion of this research was that the performance of broiler raising at 3rd floor has better performance than those at 1st floor. It is suggested to further research to determine the best production performance of broilers reared on the 1st floor, 2nd floor and 3rd floor. Keywords: depletion, microclimate, stair floors